2015
DOI: 10.1002/ajmg.a.37510
|View full text |Cite
|
Sign up to set email alerts
|

Axial skeletogenesis in human autosomal aneuploidies: A radiographic study of 145 second trimester fetuses

Abstract: Autosomal aneuploidies associate with multiple minor skeletal defects, which, in fetuses, are best appreciated post-mortem after specific anatomic preparations. The present study was aimed to define patterns of skeletal anomalies in autosomal aneuploidies at standard radiology in second trimester fetuses by comparing findings in and among genotypes and gestational ages. Aneuploid fetuses were selected for availability of radiographs of various axial and non-axial structures, mainly homeotic transformations, ve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 27 publications
0
4
2
Order By: Relevance
“…The prevalence of cervical ribs in this study population was only slightly higher (57.4%) and not very different from the study of Castori et al [15], who included the largest study population.…”
Section: Discussioncontrasting
confidence: 90%
See 2 more Smart Citations
“…The prevalence of cervical ribs in this study population was only slightly higher (57.4%) and not very different from the study of Castori et al [15], who included the largest study population.…”
Section: Discussioncontrasting
confidence: 90%
“…The prevalence of cervical ribs in cases with trisomy 21 ranged from 12.5 to 57.1% in previously reported studies [14,15,35]. The prevalence of cervical ribs in this study population was only slightly higher (57.4%) and not very different from the study of Castori et al [15], who included the largest study population.…”
Section: Discussioncontrasting
confidence: 64%
See 1 more Smart Citation
“…Recent biological and genetic studies, however, indicate that the cervical rib in early childhood is identified, in mice and in humans, as positively and significantly associated with the most frequent congenital anomalies, and several severe medical conditions [Table 5 ( Adson & Coffey 1927;Gladstone and Wakeley, 1932;Bagnall et al 1984;McNally et al 1990;Schumacher et al 1992;Keeling and Kjaer, 1999;Galis et al 2006;Bots et al 2011;Castori et al 2016, Schut et al 2019a2019b)].…”
Section: H 3 the Cervical Rib During Early Childhood A 'Morbidity Criterion'mentioning
confidence: 99%
“…Although they result from aberrations early in embryonic development, their direct clinical implications seem quite limited, except for cervical ribs, which can occasionally lead to thoracic outlet syndrome. However, they appear to be associated with both malignancies (Merks et al, ) and several congenital malformations, and have a prevalence of 75–80% in stillborn and therapeutically aborted fetuses (Ten Broek et al, ; Castori et al, ). This implies that either the Hox genes themselves—and their targets—or their upstream enhancers are more intricately involved in tissue and organ development and proliferation than has yet been established.…”
Section: Dysostosesmentioning
confidence: 99%